Generation of electricity in BFC by the biological product 'Doctor Robik' during the purification of nitrogen-containing wastewater - G.O. Zhdanova; D.I. Stom; N.Yu. Yudina; S.V. Alferov; Z.U. Dzhangidze; A.D. Stom; M.Yu. Tolstoy; I.A. Bogdanova; A.N. Chesnokova (Учёные записки Казанского университета: Серия Естественные науки)
In this study, we evaluated the efficiency of a biofuel cell technology (BFC) based on the commercial biological product “Doctor Robik 109” in the utilization of some nitrogen-containing components of wastewater (urea, ammonium nitrogen, and peptone). The following electrochemical parameters were measured during the BFC operation with “Doctor Robik 109”: voltage, current strength, power, and redox potential of the anolyte. The nitrogen-containing substrates were determined using photometric methods. The number of microorganisms was calculated by Koch’s method. It was shown that “Doctor Robik 109” generated an electric current in the BFC upon the usage of urea (0.5 g/L), ammonium nitrogen (0.5 g/L of NH4+ ions), and peptone (0.5 g/L) as substrates. The current generation by microorganisms of “Doctor Robik 109” in the BFC was accompanied by an increase in the number of cells of microorganisms, a depletion of the tested substrates, and a decrease in the redox potential of the anolyte. In the BFC containing model wastewater with the addition of 0.5 g/L of urea, “Doctor Robik 109” generated an open-circuit voltage of up to 332 mV (for 5 days). With 0.5 g/L NH4+ and 0.5 g/L peptone, this value was higher – up to 483 mV (for 1 day) and up to 520 mV (for 10 days), respectively. The current strength (in the short-circuit mode) in the BFC with urea reached 519 μA, and in the BFC with peptone it was more than two times higher (up to 1248 μA). Based on the data obtained, with an account of the breadth of the substrate specificity of microorganisms of “Doctor Robik 109”, its low cost and ease of use, recommendations were given for the use of this biological product in BFC for waste disposal and treatment of various types of wastewater with simultaneous generation of electric current.